Elemental abundance studies of CP stars. The Silicon stars HD 87405 and HD 146555 - Saffe, Carlos (2009)
In this paper we present an analysis of the Ap(Si) stars HD 87405 and HD 146555 using an ATLAS9 model atmospheres. These Chemically Peculiar (CP) stars belong to the southern hemisphere open clusters NGC 3114 and NGC 6087, respectively. For HD 87405 and HD 146555, C and Ca (only one line) are mostly solar, Mg and S are slightly underabundant, while Si is overabundant by factors between ? 4-6. Heavier elements are all overabundant, Ti, Cr by factors of ? 50, while Mn is nearly ? 50 and ? 120 times overabundant for HD 87405 and HD 146555, respectively. Fe is ? 10 times solar, Sr, Y, Zr are overabundant by factors between ? 100-1000 and rare earth by factors of ? 1000 or more. This work is part of our current study for verifying a possible tendence of abundances with the age of CP stars in open clusters.